Strategies for Achieving Climate Governance in Cameroon: A Legal Appraisal - Kum, Felix Fung (Law and Economy, 2025)
Climate governance over the last decades has occupied the minds of many scholars who are much concerned with ensuring appropriate protection of the environment. Because of the hazards and negative impact of climate change, many scholars thinks that climate governance is an unavoidable issues that society must seek to achieve. The article addresses the crucial need for effective climate governance amidst growing environmental and socio-economic challenges caused by climate change in Cameroon. Despite its commitment to international climate agreements, Cameroon faces significant legal and institutional gaps that hinder the integration of climate change considerations into national policies and sectoral plans. The research problem focuses on the absence of a comprehensive and enforceable legal framework that mandates public institutions to incorporate climate adaptation and mitigation measures into their operations, resulting in weak policy implementation and limited climate action effectiveness. The main objective is to appraise existing legal frameworks and propose strategic legal reforms that can enhance climate governance in Cameroon for sustainable development. Employing a qualitative methodology, the study reviews climate-related laws, policy documents, and stakeholder consultations to analyze gaps and opportunities in Cameroon’s climate governance architecture. Major findings reveal that while Cameroon has ratified key international conventions and developed some sectoral strategies, its legal framework remains fragmented and non-binding, with poor enforcement mechanisms. Institutional weaknesses, insufficient public participation, corruption, and lack of climate mainstreaming into budgets are prominent challenges. The study concludes that Cameroon’s climate governance can only be strengthened through comprehensive legal reforms that institutionalize climate obligations, improve coordination among ministries, and promote transparency and inclusiveness. It recommends enacting binding climate legislation, enhancing institutional capacities, ensuring public participation, and integrating climate considerations into all development policies and budgets to achieve effective climate governance aligned with sustainable development goals.